Cardiac transplantation for radiation-induced cardiomyopathy: the Mayo Clinic experience - Saxena, Pankaj; Joyce, Lyle D; Daly, Richard C; Kushwaha, Sudhir S; Schirger, John A; Rosedahl, Jordan; Dearani, Joseph A; Kara, Tomas; Edwards, Brooks S (The Annals of thoracic surgery, 2014)
BACKGROUND: High-dose radiotherapy to the mediastinum for the treatment of malignancies causes injury to the intrathoracic organs. Coronary artery disease, valvular dysfunction, cardiomyopathy, and chronic constrictive pericarditis are common cardiovascular sequelae during long-term follow-up. Cardiac transplantation is indicated for the surgical treatment of heart failure due to radiation-induced end-stage cardiac disease. METHODS: A retrospective study of radiation-induced cardiomyopathy requiring cardiac transplantation was undertaken from December 1992 to August 2010. RESULTS: Twelve patients (7 men, 5 women), with a mean age of 47.4 years, underwent orthotopic cardiac transplantation. Redo cardiac operations were performed in 9 patients. Lymphoma was the primary malignancy in all patients. Adjuvant chemotherapy was used in 9 patients, and splenectomy was performed in 7. Restrictive cardiomyopathy (n = 8) was the predominant diagnosis. Restrictive lung disease was present in 10 patients (83%). Postoperative chronic kidney injury developed in 3 patients (25%). Hospital mortality was 8.3%. Survival at 1, 5, and 10 years was 91.7%, 75%, and 46.7%, respectively. The overall mean follow-up was 7.7 years (median, 6.1; range, 1.8 to 16.4 years). Late respiratory failure accounted for 3 deaths. CONCLUSIONS: Cardiac transplantation provides satisfactory medium-term to long-term outcome in patients with radiation-induced cardiomyopathy. Secondary malignancies, kidney injury, and respiratory failure contribute to significant postoperative morbidity and death.
Keywords: kardiomyopatie; Lymphoma; Radiation Injuries; lymfom; Minnesota; Treatment Outcome; Hospital Mortality; Retrospective Studies; Time Factors; lidé středního věku; Survival Rate; lidé; časové faktory; mortalita v nemocnicích; Adult; Cardiomyopathies; Middle Aged; dospělí; následné studie; radiační poranění; Female; výsledek terapie; Graft Survival; Male; ženské pohlaví; Humans; mužské pohlaví; míra přežití; Follow-Up Studies; Heart Transplantation; přežívání štěpu; transplantace srdce; retrospektivní studie